Perancangan Sistem Pendeteksi Dan Pencegahan Penyebaran Malware Melalui SMS Gateway - Agus Tedyyana; Supria Supria (P3M Politeknik Negeri Bengkalis, 2018)
Internet network is a media or technology that is very useful at this time. Almost everyone who uses electronics using internet network. With this internet network, humans can access the virtual world with ease, either in browsing, streaming, social media access and others. On the other hand there is a lack of Internet network technology. With the internet, computers can connect with other computers, so many cases of malware attacks through the internet network. Recently there has been a very dangerous malware attack. The malware is known as wannacry ransomware. Wannacry can attack computers that use windows operating system. Computers that have been infected wannacry will make all existing data in the computer hard drive becomes encrypted, so the user can not open the data that has been infected with the virus.To solve the problem then it is proposed Design of Malware Detection and Prevention System Using Unified Modeling Language (UML). This system is designed using Router, Server, and SMS Gateway. Router is used for network configuration. The server is used for WEB-based storage systems that serve to detect ports. SMS Gateway is used to send SMS to the network admins. With the proposed system is expected to help detect the presence of malware that goes through the router, so that the system will automatically send notification of malware via SMS